The Effectiveness of Teaching According to Appleton Constructive Analytical Model in Literary Taste - AL- Saadi, Ihab Ibrahim Zaidan; Jaafa, Jasim Abd Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current research is to know the effectiveness of teaching according to Appleton Analytical Constructive Model in literary taste. In order to achieve the research goal, the researchers randomly select Al jihad prep school for boys, and by random drawing method, they chooses Class A to represent the experimental group which studies Reading according to the Appleton Analytical Constructive Model, and Class B to represent the control group that studies Reading in the traditional method. The whole sample consists of 60 students, at the rate of 30 students in each group. The researchers conduct parity between the two groups in the following variables: the age of the students calculated by months, the academic achievement of the parents, the academic achievement of the mothers, and their level of literary taste. The researchers determine the subjects that are studied during the experiment period after presenting these subjects to an elite group of experts and specialists. The researchers prepare teaching plans for the subjects to be taught during the experiment period. Two model plans are presented to a group of experts and specialists in order to know their validity and suitability. The researchers themselves teach the two research groups during the experiment period and after the end of the experiment the researchers applied the literary taste test to the students of both groups. The researchers used the following statistical means: (T-Test) with two independent samples, Kay square, and Pearson correlation coefficient. After analyzing the results, the researchers found the following: students of the experimental group who studied Reading using Appleton Analytical Constructive Model surpassed the students of the control group who studied Reading in the traditional method in the literary taste test. It was concluded that the students responded positively to Appleton Analytical Constructive Model in teaching and interacted with it through the results obtained. The researchers gave a number of recommendations, including the necessity of using Appleton Model in teaching Reading, because of its role in improving the literary appreciation of students. The researchers also gave a number of suggestions, including: Conducting a similar study in other variables such as achievement,    informationand retaining